2005
DOI: 10.1016/j.fuproc.2005.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Selection of ionic liquids for the extraction of aromatic hydrocarbons from aromatic/aliphatic mixtures

Abstract: The separation of aromatic hydrocarbons (benzene, toluene, ethyl benzene and xylenes) from C 4 to C 10 aliphatic hydrocarbon mixtures is challenging since these hydrocarbons have boiling points in a close range and several combinations form azeotropes. In this work, we investigated the separation of toluene from heptane by extraction with ionic liquids. , are a factor of 1.5 -2.5 higher compared to those obtained with sulfolane (S tol/hept = 30.9, D tol = 0.31 at 40 -C), which is the most industrially used sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
291
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(317 citation statements)
references
References 50 publications
16
291
4
Order By: Relevance
“…The vessels were closed with a PVC-cover through which a stirrer shaft was lead. For each experiment 10 ml of the feed and 20 ml ionic liquid have been added and the mixture was stirred (1200 rpm) for 15 min to reach equilibrium [5]. After stirring, the two phases were allowed to settle for about 1 h. For phase mixing two stainless steel propellers, one in the bottom phase and one at the phase interface, with an electronic stirrer (Ika Eurostar) were used.…”
Section: Equipment and Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The vessels were closed with a PVC-cover through which a stirrer shaft was lead. For each experiment 10 ml of the feed and 20 ml ionic liquid have been added and the mixture was stirred (1200 rpm) for 15 min to reach equilibrium [5]. After stirring, the two phases were allowed to settle for about 1 h. For phase mixing two stainless steel propellers, one in the bottom phase and one at the phase interface, with an electronic stirrer (Ika Eurostar) were used.…”
Section: Equipment and Experimental Proceduresmentioning
confidence: 99%
“…In order to maintain constant temperature (±0.1 K) a water bath (Julabo F32-MW) was used. A more detailed description of the experimental procedure was reported earlier by Meindersma et al [5].…”
Section: Equipment and Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the liquidliquid extraction of metal ions from water by ionic liquids containing metal-coordination agents and the separation of aromatics from alkanes by hydrophilic ionic liquids have been studied in detail. 36,37 However, solid adsorbents are highly advantageous for separation because of their ease of manipulation, the lack of limits on solvent miscibility and the lower consumption of volatile organic solvents. 38,39 Furthermore, the use of biphasic extraction systems requires the use of large amount of ionic liquids.…”
Section: Preparation Of Ionic Liquid-modified Sba-15 Adsorbentsmentioning
confidence: 99%
“…[12] Meindersma et al reported on the extraction of aromatic hydrocarbons from aromatic/aliphatic mixtures by selecting suitable ILs. [13] Electrochemiluminescence (ECL) is a means of converting electrical energy into radiative energy. It involves the production of reactive intermediates from stable precursors at the surface of an electrode via an applied voltage.…”
Section: Introductionmentioning
confidence: 99%